Enhancing Students' Speaking Skills in Describing People through the Presentation-Practice-Production (PPP) Method at SMP Negeri 5 Sigi - Angraeni, Nining; Nur Asmawati, Nur Asmawati; Zuhra, Zuhra (Datokarama English Education Journal, 2023)
This study addresses the students' need for enhanced speaking skills, particularly in terms of fluency. The inquiry posed in this thesis originates from the question: Can the application of the Presentation, Practice, and Production (PPP) method contribute to the improvement of students' speaking abilities when describing a person at SMP Negeri 5 Sigi? The objective is to ascertain whether the use of the PPP method has a positive impact on students' proficiency in describing individuals. The research adopts a quantitative approach through quasi-experimental methods. The study encompasses the eighth-grade students of SMP Negeri 5 Sigi, comprising three classes. The experimental class comprises 20 students, while the control class consists of 20 students. Purposive sampling is employed to select students from classes VIII A and VIII B. The research findings demonstrate that the utilization of the Presentation Practice Production (PPP) method significantly enhances students' speaking skills, specifically in terms of fluency. This is evident from the mean scores of the experimental and control classes, which are 17.65 and 8.9, respectively. The calculated t-value of 4.26, with a degree of freedom (df) of 38 (20+20-2) and a significance level of 0.05, surpasses the critical t-table value of 2.00. Consequently, the hypothesis of the research is accepted, affirming that the implementation of the Presentation Practice Production method is effective in improving the speaking skills of eighth-grade students at SMP Negeri 5 Sigi.